The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1021/ja202268t
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Polymerization from Polypeptide-Grafted Comb Polymers

Abstract: The helical and tubular structures self-assembled from proteins have inspired scientists to design synthetic building blocks that can be "polymerized" into supramolecular polymers through coordinated noncovalent interactions. However, cooperative supramolecular polymerization from large, synthetic macromolecules remains a challenge because of the difficulty of controlling the structure and interactions of macromolecular monomers. Herein we report the synthesis of polypeptide-grafted comb polymers and the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 36 publications
2
47
0
Order By: Relevance
“…When pH decreases, carboxyl groups are protonated. The polymer then adopts a helical conformation and becomes insoluble in water [3,13,14] . This phase-transition could be adjusted by copolymerization Glu with hydrophobic amino acids [15] .…”
Section: Introductionmentioning
confidence: 99%
“…When pH decreases, carboxyl groups are protonated. The polymer then adopts a helical conformation and becomes insoluble in water [3,13,14] . This phase-transition could be adjusted by copolymerization Glu with hydrophobic amino acids [15] .…”
Section: Introductionmentioning
confidence: 99%
“…PGA can adopt different solution conformations depending on the degree of ionization, while pH represents a critical parameter for controlled supramolecular polymerization. 28,29 We performed circular dichroism studies of F3E10 at pH 7.5 (Fig. SI1 †) and observed that PGA adopts a random coil conformation.…”
Section: Polymer Chemistry Papermentioning
confidence: 99%
“…Wang et al have found conditions where polypeptidegrafted comblike polymers form tubular structures. [12] Moreover, they found that gold nanoparticles with grafted poly-(L-glutamic acid) can form tubules under certain circumstances. [12,13] In these systems, the monomer is effectively a single nanoparticle and the nanoparticle-nanoparticle interactions dictate the tubule formation.…”
Section: Introductionmentioning
confidence: 99%